Desarrollo de un sistema web para la gestión de historias clínicas y asistencia telemática mediante un chatbot utilizando la metodología Lean Thinking Developer en la clínica veterinaria “Mundo Mascotas” del Cantón Guaranda - Luna Arteaga, Alexander Paul (2024)
This project focused on implementing a web system aimed at improving the clinical record management processes and telematic assistance at the "Mundo Mascotas" veterinary clinic. To achieve this purpose, the Lean Thinking Developer methodology was adopted, consisting of four main phases: Research: In this stage, information gathering techniques were employed to obtain the necessary requirements. Design: Techniques were used to design interfaces and select the most appropriate software architecture. Implementation: Software development was carried out to ensure the proper execution of the web system. Testing: The owners of the veterinary clinic performed tests on the system, validating its quality, usability, and scalability. The MediVen web system contributes to the agile management of clinical records and telematic assistance at the "Mundo Mascotas" clinic. It considers data security, software quality, and usability to provide the best possible user experience.